Echocardiographic phenomenon “RAC-sign” in the anomalous course of circumflex artery: a case report - K. V. Skaletsky; A. M. Namitokov; E. K. Donets; S. V. Kruchinova; V. A. Gagin; E. D. Kosmacheva (Российский кардиологический журнал, 2022)
Coronary artery (CA) anomalies are a group of congenital heart defects  with a diverse clinical performance, from lifelong asymptomatic to severe consequences such as sudden cardiac death. In some cases,  CA anomalies become  an incidental finding during echocardiography.  If there is a suspicion of CA anomaly, a radiographic investigation (computed tomography (CT) angiography or magnetic resonance imaging) should be performed to clarify the anatomy and indications for surgical correction.A case of diagnosing a tubular structure with hyperechoic  walls in mitral valve projection during echocardiography  is presented. The performed CT angiography confirmed the abnormal origin of circumflex artery from the right sinus of Valsalva with its retroaortic course. This echocardiographic  sign is described in the English-language literature as Retroaortic Anomalous Coronary sign (RAC-sign).